Heritage Stone 9. Tyndall Stone, Canada’s First Global Heritage Stone Resource: Geology, Paleontology, Ichnology and Architecture - Pratt, Brian R.; Young, Graham A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2023)
Tyndall Stone is a distinctively mottled and strikingly fossiliferous dolomitic limestone that has been widely used for over a century in Canada, especially in the Prairie Provinces. It comprises 6–8 m within the lower part of the 43 m thick Selkirk Member of the Red River Formation, of Late Ordovician (Katian) age. It has been quarried exclusively at Garson, Manitoba, 37 km northeast of Winnipeg, since about 1895, and for the past half-century extraction has been carried out solely by Gillis Quarries Ltd. The upper beds tend to be more buff-coloured than the grey lower beds, as a result of groundwater weathering. Tyndall Stone, mostly with a smooth or sawn finish, has been put to a wide variety of uses, including exterior and interior cladding with coursed and random ashlar, and window casements and doorways. Split face finish and random ashlar using varicoloured blocks split along stylolites have become popular for commercial and residential buildings, respectively. Tyndall Stone lends itself to carving as well, being used in columns, coats of arms and sculptures. Many prominent buildings have been constructed using Tyndall Stone, including the provincial legislative buildings of Saskatchewan and Manitoba, the interior of the Centre Block of the House of Commons in Ottawa, courthouses, land titles buildings, post offices and other public buildings, along with train stations, banks, churches, department stores, museums, office buildings and university buildings. These exhibit a variety of architectural styles, from Beaux Arts to Art Deco, Châteauesque to Brutalist. The Canadian Museum of History and the Canadian Museum for Human Rights are two notable Expressionist buildings.The lower Selkirk Member is massive and consists of bioturbated, bioclastic wackestone to packstone, rich in crinoid ossicles. It was deposited in a low-energy marine environment within the photic zone, on the present-day eastern side of the shallow Williston Basin, which was part of the vast equatorial epicontinental sea that covered much of Laurentia at the time. Scattered thin bioclastic grainstone lenses record episodic, higher energy events. Tyndall Stone is spectacularly fossiliferous, and slabs bearing fossils have become increasingly popular. The most common macrofossils are receptaculitids, followed by corals, stromatoporoid sponges, nautiloid cephalopods, and gastropods. The relative abundance of the macrofossils varies stratigraphically, suggesting that subtle environmental changes took place over time.The distinctive mottles—‘tapestry’ in the trade—have been regarded as dolomitized burrows assigned to Thalassinoides and long thought to have been networks of galleries likely made by arthropods. In detail, however, the bioclastic muddy sediment underwent a protracted history of bioturbation, and the large burrows were mostly horizontal back-filled features that were never empty. They can be assigned to Planolites. The matrix and the sediment filling them were overprinted by several generations of smaller tubular burrows mostly referrable to Palaeophycus due to their distinctive laminated wall linings. Dolomite replaced the interiors of the larger burrows as well as smaller burrows and surrounding matrix during burial, which is why the mottling is so variable in shape.